The Implementation of Gamification Method in Blended Learning - Mawarni, Sella; Hartoto, Hartoto (Indonesian Journal of Educational Studies, 2022)
The study aims to describe the implementation of gamification method in blended learning which is carried out during one semester in the Educational Technology study program. This study used descriptive qualitative method. The research population consisted of 82 students of Education Technology class of 2021. Data was collected using the documentation method, and a questionnaire through Google Forms. The data were analyzed and interpreted in a descriptive qualitative manner by referring to the formulation of the problem set. The result showed the following; blended learning that applies the gamification method is considered more fun, facilitates learning and increases student engagement during the learning process. The learning stages that need to be done to apply the gamification method in learning are determining the characteristics of the learner, determining the learning objectives to be achieved, creating gamification-based learning content and activities, and adding game elements and mechanisms.